Structure and functioning of fish assemblages in two South African estuaries, with emphasis on the presence and absence of aquatic macrophyte beds - Sheppard, Jill Nicole (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2010)
Temporarily open/closed estuaries (TOCEs) are the dominant estuary type in South Africa. These systems are often characterized by extensive beds of submerged macrophytes, which form important foraging and shelter habitats for fishes, especially for estuary-dependent fish species such as the Cape stumpnose Rhabdosargus holubi and Cape moony Monodactylus falciformis that are commonly associated with them. A loss of submerged macrophytes from an estuary has been shown to affect the fish community as well as reducing overall system productivity. The TOC East Kleinemonde Estuary, situated in the warm-temperate biogeographic region of South Africa has been subject to an ongoing long-term fish monitoring project since 1995. During the period 1995 to 2002, this estuary contained large beds of the submerged macrophytes Ruppia cirrhosa and Potamogeton pectinatus. However, subsequent to a major flood event in 2003 these macrophytes have been largely absent from this system. The effect of the loss of submerged macrophytes on the East Kleinemonde fish assemblage was investigated through an analysis of seine and gill net catch data. Seine net catches for a 12 year period, encompassing six years of macrophyte presence and six years of macrophyte senescence, revealed changes in the relative abundance of certain fish species. Vegetation-associated species such as R. holubi and M. falciformis decreased in abundance whereas sediment-associated species, especially members of the family Mugilidae, increased in abundance following loss of the macrophytes in this estuary. The critically endangered pipefish Syngnathus watermeyeri was only recorded in catches during years in which macrophyte beds were present. In addition to the analysis of catch data, the importance of macrophytes as a primary energy source for selected estuarine fishes was explored through the analysis of carbon and nitrogen stable isotopes. Prior to conducting these analyses, common methodological practices to address the presence of carbonates and lipids within isotope samples were evaluated. A subset of samples were either acid washed to remove carbonates, or lipids were removed according to the method of Bligh and Dyer (1959) as both of these compounds have been shown to affect stable carbon and nitrogen isotope ratios. The suitability of the lipid normalization models of Fry (2002) and Post et al. (2007) for samples of estuarine fish muscle were also tested. Based on this evaluation both models are suitable for use with estuarine fish muscle tissue, however since neither carbonate nor lipid content of any of the samples used in this study was high all samples were left untreated in the following analysis. Carbon isotope ratios from a wide range of fish species collected from the East Kleinemonde Estuary during the macrophyte-senescent phase were compared with individuals of the same species from the neighbouring West Kleinemonde Estuary (where extensive beds of R. cirrhosa and P. pectinatus were present) and revealed the influence of submerged macrophyte material in the diet of fishes in the latter system. However, it was apparent that these plants are not directly consumed but rather contribute to the detrital pool that forms a food source for most invertebrate and some fish species. The most significant source of carbon for East Kleinemonde fishes during the macrophyte senescent phase appeared to have a more depleted origin; probably from benthic or pelagic microalgae. In conclusion, while the importance of macrophyte beds as shelter and foraging habitats for estuarine fishes are well documented, their role in terms of the structuring and functioning of fish assemblages in TOCEs remains somewhat uncertain. The findings of this study were possibly masked by the resilience of vegetation-associated species to the loss of this habitat, as well as by life history characteristics of species such as R. holubi that allow their numerical dominance despite habitat change. Nonetheless, macrophyte senescence in the East Kleinemonde Estuary resulted in the loss of at least one species and the reduced abundance of vegetation-associated species, probably reflective of reduced food resources and/or increased vulnerability to predation. As a result, beds of submerged macrophytes are an important habitat within TOCEs.
Keywords: Estuaries -- South Africa -- Eastern Cape; Estuarine ecology -- South Africa -- Eastern Cape